REALISASI SARANA POJOK BELAJAR UNTUK MENINGKATKAN PROSPEK KESADARAN LITERASI USIA DINI DIDESA TIMPAH - Hidayati, Sri; Qori, Husna Misbahul; Ramadhani, Windy Arina Dewi; Jannah, Hikmatul; Sandi, Kurnia; Pangestu, M. Adjie; Nurlita, Tiara Ayu; Nurmajidah, Nurmajidah; Dntiarmaya, Annisa Ayu; Norliana, Norliana; Rahmad, Rahmad (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The importance of teaching reading, counting and writing skills from an early age. Learning from an early age, to help Timpah village children develop good habits that they can maintain even when things get difficult. The Basama learning corner literacy movement can bring change. Focus on teaching reading, counting and writing skills to students and teaching them reading, counting and writing skills. This article explains the Realization of Learning Corner Facilities to Increase the Prospects of Early Childhood Literacy Awareness in Timpah Village. In implementing the service that we have carried out, the methodology used is Sisdamas or Community Empowerment Based. The results of this research show that mentoring has a positive impact on improving the reading, writing and arithmetic abilities of Timpah Village children. With the activities held by IAIN Palangkaraya KKN students, as a driving force in the Learning Corner held by Timpah Village. Such as teaching reading, writing, arithmetic (calistung) activities, with this, the people of Timpah Village, especially children, are more interested in learning and experiencing good improvements in terms of reading, writing and arithmetic (calistung). Based on the activities carried out by the group of 69 Real Work Lectures (KKN) at the Palangka Raya State Islamic Institute (IAIN) in Timpah Village, it can be concluded that the program to provide Basama Learning Corner facilities to increase literacy for children in Timpah Village is running. smoothly. This activity has a significant impact on the literacy skills of children in Timpah Village.